Another new species of Glossocephalus (Crustacea: Amphipoda: Hyperiidea: Oxycephalidae) from the Monterey Bay region, California, USA - Zeidler, Wolfgang; Browne, William E. (Zootaxa, 2023)
A new species of Glossocephalus, G. aurantium sp. nov., is described based on two female specimens collected from the Monterey Canyon, California, eastern Pacific Ocean. It was found associated with an undescribed lobate ctenophore. Glossocephalus aurantium is readily distinguished from its congeners by the large crescent-shaped bulbous eye fields relative to the size of the head capsule. The pereopod morphology is most similar to G. rebecae, recently described from the same general region by Zeidler and Browne (2015), but that species is readily distinguished by it’s relatively narrow crescent-shaped eye fields. Apart from it’s prominent bulbous eye structures, G. aurantium is distinguished from G. milneedwardsi by the morphology of the gnathopods (not spoon-shaped). In addition, pereopods 5 and 6 are slender (not paddle-like) and the head capsule is relatively larger with a sharp rostrum (not rounded).